Anaesthesia for ophthalmic procedures in patients with thyroid eye disease. Issue 6 (November 2020) - Chua, Alfred WY; Kumar, Chandra M; Chua, Matthew J; Harrisberg, Brian P
Thyroid eye disease is an autoimmune inflammatory disorder of the orbit in adults. It causes inflammation, expansion and fibrosis of orbital fat, muscles and the lacrimal gland, leading to facial disfigurement, functional disability and, in severe cases, blindness. Overall, approximately 20% of affected patients need some form of surgical intervention requiring anaesthesia. This narrative review explores the background of thyroid eye disease, surgical procedures performed and their implications for anaesthesia. General anaesthesia is used for orbital decompression procedures, strabismus correction surgery and complex oculoplastic procedures. Local anaesthetic infiltration or regional anaesthesia under monitored anaesthesia care are the techniques most commonly employed for eyelid retraction surgery. It is important to limit the volume of local anaesthetic agent used during infiltration and continuously monitor the orbital volume and ocular pressure with a ballottement technique. In addition, the contralateral eye should be checked and, if necessary, protected against corneal exposure. Retrobulbar, peribulbar and sub-Tenon's blocks are best avoided. Topical anaesthesia has been used for some strabismus correction surgery but its use is limited to motivated and cooperative patients only.